A method to convert non-numeric characters into numerical values in dynamic time warping for string matching - Hyun Jun Park (International Journal of Electrical and Computer Engineering (IJECE), 2021)
Dynamic time warping (DTW) is one of the well-known algorithms for measuring similarity between two temporal sequences, and it can be used for character matching. It uses a distance of two character strings. However, since the characters are non-numeric, it must be assigned to numerical values to calculate a distance between two character strings. Therefore, in this paper, we propose a method to convert non-numeric characters into numerical values in dynamic time warping for string matching. The proposed method uses normalized correlation coefficient, and it makes DTW gives more accurate results. Experimental results show that the proposed method gives excellent results.